Anxiety predicts internet addiction, which predicts depression among male college students: A cross-lagged comparison by sex - Xie, Xiaoqian; Cheng, Hui; Chen, Zi (Frontiers in Psychology, 2023)
Objectives: Internet addiction has become an increasingly serious public health issue, putting young people at particular risk of psychological harm. This study aimed to analyze the interactions between college students' depression, anxiety, and Internet addiction and explore how these interactions differ between men and women. Methods: A 6-month follow-up study was conducted on 234 college students using the Self-Rating Depression Scale, Self-rating Anxiety Scale, and Revised Chen Internet Addiction Scale. Results: Depression, anxiety, and Internet addiction were positively correlated (P<0.01). Anxiety can predict Internet addiction and that Internet addiction can predict depression. Moreover, anxiety had a significant predictive effect on Internet addiction among men. Conclusions: Anxiety predicts Internet addiction, and Internet addiction predicts depression among male college students. These findings may better inform future Internet addiction intervention strategies. Particularly, interventions may better address Internet addiction by focusing on the role of anxiety, especially among men.